The Use of Unlisted Billing Codes for Microsurgical Breast Reconstruction and Implications for Code Consolidation - Yang, Alan Z.; Hyland, Colby J.; Carty, Matthew J.; Erdmann-Sager, Jessica; Pusic, Andrea L.; Broyles, Justin M. (Journal of Reconstructive Microsurgery, 2024)
Background Private insurers have considered consolidating the billing codes presently available for microvascular breast reconstruction. There is a need to understand how these different codes are currently distributed and used to help inform how coding consolidation may impact patients and providers.Methods Using the Massachusetts All-Payer Claims Database between 2016 and 2020, patients who underwent microsurgical breast reconstruction following mastectomy for cancer-related indications were identified. Multivariable logistic regression was used to test whether an S2068 claim was associated with insurance type and median household income by patient ZIP code. The ratio of S2068 to CPT19364 claims for privately insured patients was calculated for providers practicing in each county. Total payments for professional fees were compared between billing codes.Results There were 272 claims for S2068 and 209 claims for CPT19364. An S2068 claim was associated with age < 45 years (OR: 1.89, 95% CI: 1.11–3.20, p = 0.019), more affluent ZIP codes (OR: 1.11, 95% CI: 1.03–1.19, p = 0.004), and private insurance (OR: 16.13, 95% CI: 7.81–33.33, p < 0.001). Median total payments from private insurers were 101% higher for S2068 than for CPT19364. In all but two counties (Worcester and Hampshire), the S-code was used more frequently than CPT19364 for their privately insured patients.Conclusion Coding practices for microsurgical breast reconstruction lacked uniformity in Massachusetts, and payments differed greatly between S2068 and CPT19364. Patients from more affluent towns were more likely to have S-code claims. Coding consolidation could impact access, as the majority of providers in Massachusetts might need to adapt their practices if the S-code were discontinued.
Keywords: microsurgical; breast reconstruction; DIEP; 19364; S2068; S-code; billing; reimbursement